MOST IMPORTANT FACTORS IN LEARNING ENGLISH AS A SECOND LANGUAGE (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Learning a second language, particularly English, is a significant endeavor in today's globalized world. This article explores the most important factors affecting the acquisition of English as a second language. Through a literature analysis, we identify key elements that impact language learning. We also present various methods and strategies employed by language learners and teachers to facilitate the process. The study discusses the results of these methods and their implications for successful language acquisition. Finally, we offer conclusions and suggestions for individuals seeking to learn English as a second language.